Transforming a mediaeval university - MacColl, John A. (Henry Stewart Talks, 2012)
Ancient and mediaeval universities, Scottish ancient university libraries, University library history, Digital resources, The digital revolution, Cloud libraries, From library 'holdings' to licensed content, Publisher pricing policies, Scholarly journals, From 'the online library' to resources on the web, Open access repositories, Hybrid libraries, Special collections, Rare and unique materials, University archives, Scale developments in library operations, History of legal deposit, National and international library cooperation, Global competition in higher education, Cataloguing of special collections, Digitization of special collections, Contrast with US research university libraries, Library branding